Variation of Open-Pit Waste Dump Specimens Under Effective Pressure Influence - Tovele, Gerson. S. V.; Han, Liu; Shu, Ji Sen (Frontiers in Earth Science, 2021)
The waste dump is a giant artificial loose pile body composed of fine, medium, and coarse particle sizes. Rising incidents of landslides caused by overburden pressure and effective pressure are of increasing concern in the open-pit waste dump and, if not well-controlled, are a dangerous threat to the workers, the environment, and the equipment. The purpose of this research is to investigate the connection between effective pressure, porosity, void ratio, and coefficient of permeability and to find their influence in the open-pit waste dump. This study analyzed the mechanical and physical changes of seven different soil samples using consolidation and permeability under consolidation laboratory test. The test samples were subject to a pressure ranging from 100 to 1600 kPa. The effective pressure was found to play a major role in influencing void ratio, porosity, and coefficient of permeability, and waste dump height management and control are of great importance. This study answers the question regarding the correlation between effective pressure, void ratio, porosity, and coefficient of permeability in the open-pit waste dump. Further studies are needed to establish profound relationships and develop preventative measures to keep the waste dump slope stable and safe.